Exploring the perspectives of pharmaceutical experts and healthcare practitioners on senolytic drugs for vascular aging-related disorder: a qualitative study - Wong, Li Ping; Alias, Haridah; Tan, Kit Mun; Wong, Pooi Fong; Murugan, Dharmani Devi; Hu, Zhijian; Lin, Yulan (Frontiers in Pharmacology, 2023)
The field of targeting cellular senescence with drug candidates to address age-related comorbidities has witnessed a notable surge of interest and research and development. This study aimed to gather valuable insights from pharmaceutical experts and healthcare practitioners regarding the potential and challenges of translating senolytic drugs for treatment of vascular ageing-related disorders.Methods: This study employed a qualitative approach by conducting in-depth interviews with healthcare practitioners and pharmaceutical experts. Participants were selected through purposeful sampling. Thematic analysis was used to identify themes from the interview transcripts.Results: A total of 6 individuals were interviewed, with 3 being pharmaceutical experts and the remaining 3 healthcare practitioners. The significant global burden of cardiovascular diseases presents a potentially large market size that offer an opportunity for the development and marketability of novel senolytic drugs. The pharmaceutical sector demonstrates a positive inclination towards the commercialization of new senolytic drugs targeting vascular aging-related disorders.However potential important concerns have been raised, and these include increasing specificity toward senescent cells to prevent off-site targeting, thus ensuring the safety and efficacy of these drugs. In addition, novel senolytic therapy for vascular aging-related disorders may encounter competition from existing drugs that treat or manage risk factors of cardiovascular diseases.Healthcare practitioners are also in favor of recommending the novel senolytic drugs for vascular ageing-related disorders but cautioned that its high cost may hinder its acceptance among patients.Besides sharing the same outcome-related concerns as with the pharmaceutical experts, healthcare practitioners anticipated a lack of awareness among the general public regarding the concept of This is a provisional file, not the final typeset article targeting cellular senescence to delay vascular aging-related disorders, and this knowledge gap extends to healthcare practitioner themselves as well.Senolytic therapy for vascular ageing-related disorders holds great promise, provided that crucial concerns surrounding its outcomes and commercial hurdles are effectively addressed.